Well-Informed Choices? Effects of Information Interventions in Primary Care on Care Quality - Anders Anell; Jens Dietrichson; Lina Maria Ellegård; Gustav Kjellsson (Lund University, School of Economics and Management, Department of Economics, 2022)
Market frictions, such as imperfect information or hassle costs, may reduce benefits from market incentives in healthcare settings. We use data from two randomised policy interventions in a Swedish region, which improved the access to provider information and reduced the switching costs of one percent of the adult population and of a sample of new residents. We examine the effects of the interventions on a large number of clinical process quality measures, access to care, and adverse health events, measured at the individual level. We find no significant effect of the interventions on any of the quality measures.
Keywords: D89; I11; 330; Market frictions; Field experiment; Care quality; Primary care; Sweden